[3]‐1‐Azadendralenes as Versatile Building Blocks for the Stereoselective Synthesis of Polysubstituted Hexahydroquinazolin‐2‐ones and Hexahydrobenzothiazine‐2‐imines. Issue 20 (2nd June 2015) - Kobayashi, Satoru; Kudo, Kenji; Ito, Ai; Honjo, Takuya; Yata, Masahiro; Otani, Takashi; Kutsumura, Noriki; Saito, Takao; Berrée, Fabienne; Romain, Elise; Tripoteau, Fabien; Carboni, Bertrand
Abstract: A diene‐transmissive hetero‐Diels–Alder reaction of cross‐conjugated 1‐azatrienes (3 ‐1‐azadendralenes) is described for the synthesis of hexahydroquinazolin‐2‐ones and hexahydrobenzothiazine‐2‐imines derivatives. [4+2] Cycloaddition reactions with tosyl isocyanate or aryl isothiocyanates gave mono‐cycloadducts with high chemo‐ and regioselectivities. The second Diels–Alder reaction with representative dienophiles, tetracyanoethylene, N ‐phenylmaleimide, and methyl vinyl ketone, stereoselectively produced ring‐fused nitrogen heterocycles. Skeletal diversity can be accessed by combining the three reaction partners – primary amine, tosyl isocyanate, and cross‐conjugated 1‐oxatriene – in a different sequential order. Abstract : The diene‐transmissive hetero Diels–Alder reaction of cross‐conjugated 1‐azatrienes was developed to produce stereoselectively ring‐fused nitrogen heterocycles. [4+2] cycloaddition reaction with tosyl isocyanate or aryl isothiocyanates gave regioselectively monocycloadducts that reacted with dienophiles. Skeletal diversity is achieved by the addition sequence of the three reaction partners.